VD_FINDINFO HC / 2019 / 316 vom 25. März 2019 - VD Tribunal cantonal (2019)
RETRAITVOIE DE DROIT, RADIATION DU RÔLE, FRAIS JUDICIAIRES, DÉPENS | 105 al. 1 CPC (CH), 106 al. 1 CPC (CH), 241 al. 3 CPC (CH), 65 al. 3 TFJC (2010), 67 al. 1 TFJC (2010), 20 al. 2 TDC